Prospects for Economic Development of Regions on the Basis of Uzbekistan Experience - Azimov, Rustam (European Journal of Applied Sciences, 2025)
This paper examines theoretical and methodological issues of regional development as an important part of national territories and economics. Conducted a study of the basic functions of governments on regional development and necessary measures. The main measures for the development of regions are considered using the example of the People’s Republic of China, the Federal Republic of Germany and the Republic of Uzbekistan, based on the inherent territorial specificity and general socio-economic development of these countries. The author examines the factors slowing down regional development, and also provides conclusions and suggestions on effective and integrated development of regions.